The Role of Sports in A Healthy Lifestyle - Saribayev Shuxrat Turdibekovich (Peerian Journals Publishing, 2022)
Our Republic places a high priority on the development of healthy progeny after focusing on freedom. The physical education of young people is one of the primary aspects receiving attention in the development of a healthy generation. Physical education is a crucial component of general education since it aids in educating children in all facets of moral and spiritual vitality. the outcome of physical education, which is itself a product of civilization at large. Physical education is one of the keys focuses of the contemporary education of youth as enlightened, spiritually in demand. The opinions and considerations on how sports fit into leading a healthy lifestyle are retained in this article.
Keywords: Healthy living,; sports; importance; education